1993
DOI: 10.1111/j.1365-2885.1993.tb00175.x
|View full text |Cite
|
Sign up to set email alerts
|

The disposition of suxibuzone in the horse

Abstract: A high performance liquid chromatographic method is described to determine the anti-inflammatory drug suxibuzone (SXB) and its major metabolites phenylbutazone (PBZ) and oxyphenbutazone (OPBZ) in equine plasma and urine. When suxibuzone (6 mg/kg) was administered intravenously (i.v.) or orally (p.o.) no parent drug was detected in plasma or in urine. The disposition of the metabolite PBZ (i.v.) could be described by a 2 compartment model with a beta half-life varying from 7.40 to 8.35 h. Due to severe side eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…Most reported studies are focused on the SBZ's pharmacokinetic profile and its toxicological potential after i.v. or oral administration in the horse (Delbeke et al 1993;Jaraiz et al 1999a,b;Mayós 2002;Monreal et al 2004). To our knowledge there are no other published studies reporting controlled clinical field trials comparing the effectiveness of SBZ and PBZ in horses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reported studies are focused on the SBZ's pharmacokinetic profile and its toxicological potential after i.v. or oral administration in the horse (Delbeke et al 1993;Jaraiz et al 1999a,b;Mayós 2002;Monreal et al 2004). To our knowledge there are no other published studies reporting controlled clinical field trials comparing the effectiveness of SBZ and PBZ in horses.…”
Section: Discussionmentioning
confidence: 99%
“…In veterinary medicine, SBZ has been used for many years in several animal species, including dogs (McKellar et al 1991) and horses (Delbeke et al 1993;Jaraiz et al 1999a,b;Rendle 2006). In horses, SBZ is converted to PBZ and oxyphenbutazone immediately after its absorption from the GI tract (Mayós 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid disappearance of SBZ from equine plasma could reflect extensive first‐pass metabolism in the liver as in vitro studies have indicated that equine plasma esterases induced no significant SBZ breakdown ( Shindo et al ., 1979 ; Houin, 1990; Baggot, 1992; Delbeke et al ., 1993 ). Results of this study are consistent with the reported high capacity to hydrolyse SBZ and concurrent formation of PBZ after intravenous administration ( Jaraiz et al ., 1999 ) and during the in vitro incubation with horse liver homogenates ( Delbeke et al ., 1993 ). In addition, orally administered SBZ might be hydrolysed to PBZ by intestinal mucosal esterases before transfer to the portal vein, as has been suggested in rats and rabbits ( Shindo et al ., 1979 ).…”
Section: Discussionmentioning
confidence: 99%
“…In humans and animals, suxibuzone is metabolised to PBZ and OPBZ following intravenous or oral administration ( Shindo et al ., 1979 ; Taira et al ., 1980 ; Delbeke et al ., 1993 ); however, some important pharmacokinetic differences between species have been reported. It has been shown that SBZ is immediately metabolised to PBZ when administered orally to rats, rabbits, dogs, monkeys and humans, though in humans, dogs and monkeys only a small amount of SBZ could be detected in plasma during the early time of dosing.…”
Section: Introductionmentioning
confidence: 99%
“…5 Los fenotiacínicos pueden ocasionar disminución en el hematócrito y en las proteínas plasmáticas totales, posiblemente por secuestro a nivel esplénico. 46 La propionilpromacina (fenotiacínico), al utilizarse como preanestésico en anestesia con halotano, ocasionó mayor hipotensión sistólica y problemas locomotores posoperatorios en comparación con la xilazina. 47 Cuando se administra acepromacina por vía oral se ven menos afectados los parámetros de presión arterial media, frecuencia cardiaca y respiratoria y cuenta hemática, en comparación con la administración iv.…”
Section: Fenotiacínicosunclassified